Chapter 5.14 Research Management and Administration in Pakistan's Context - Mir Asghar Ali Khan (Emerald Publishing Limited, 2023)
Pakistan, being a developing country, still has a long way to go to see progress in the field of research managers and administrators (RMAs). This chapter briefly explains the profession's ecosystem in the country, its evolution, available data, and the future of the field. The type and quantum of extramural research happening in Pakistan are quite significant in terms of the number of grants as well as the total annual funding. Despite this progress, the growth of research management and administration as a profession is slow-paced because of the lack of recognition of RMAs as a profession, complemented by the dearth of schools that teach this formally in the country. The future, however, sounds promising as more and more people are gradually undertaking this dynamic field and working formally to acquire the knowledge and skills to become better research management and administration professionals.
10.1108/978-1-80382-701-820231048; 10.1108/978-1-80382-701-820231048; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262